Antibiotic Resistance and Detection of the fimH Gene in E. coli Isolated from Urinary Tract Infection Patients in Surabaya, Indonesia - Rini Purbowati; Sri Lestari; Agusniar Furkani (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2026)
with fatal infections worldwide, including uropathogenic E. coli (UPEC), which causes Urinary Tract Infections (UTIs). UPEC has a specific set of virulence genes, one of which is the type 1 pilus (fimH adhesin), which mediates bacterial adhesion to the bladder epithelium, resulting in bacterial growth and colonization. fimH also has potential as a vaccine target for UTI to reduce the high rate of multidrug resistance. The aim of this research is (1) to determine the resistance level of E. coli isolates from UTI patients to amoxicillin, ciprofloxacin, and gentamicin antibiotics, and (2) to evaluate the presence of the fimH gene encoding the adhesion factor in these isolates. Methods: This study is an experimental laboratory study. The determination of antibiotic resistance levels to amoxicillin, ciprofloxacin, and gentamicin uses the CLSI’s disc diffusion methods. The presence of the fimH gene (gene ID: 948847) was determined by Polymerase Chain Reaction (PCR). Results: The tested UPEC showed the greatest resistance to amoxicillin (92%), followed by ciprofloxacin (88%) and gentamicin (56%). Additionally, molecular identification showed that 49 of 50 isolates (98%) were positive for fimH. Conclusion: Escherichia coli isolated from patients with urinary tract infections showed the highest resistance to amoxicillin, followed by ciprofloxacin and gentamicin. At the same time, the fimH gene encoding the adhesion factor was also highly prevalent.